The implementation of Jesus' transformative leadership in leaders and activists of the Protestant Christian church in Bali, Indonesia - I Ketut Darsana; Muner Daliman; Suwarsono Warnomartoyo; Sri Wahyuni; Jamin Tanhidy (International Journal of Humanities and Innovation (IJHI), 2021)
Jesus Christ is a role model for leaders, with His leadership still relevant until now. Jesus brought transformation to His community, and this transformative leadership model is needed to renew church ministry and evangelism. This article aims to find out the level of implementation of Jesus' transformative leadership among church leaders and activists of the Protestant Christian Church in Bali (GKPB) at Denpasar. This “traditional” church needs transformation to improve its quality and range of services outside Bali Island. The research used a quantitative method by measuring the Four Dimensions (D) in the concept of transformative leadership of Jesus according to the Gospel of Matthew. Results show that first, the implementation of Jesus' transformative leadership among GKPB Denpasar leaders and activists was found to be in "moderate" level due to the leadership model that was still committed to the system of institutional centralization and local autonomy based on tradition, which became an obstacle to develop mission work outside Bali. Second, the implementation of Jesus' transformative leadership among GKPB Denpasar leaders and activists was more dominantly influenced by the understanding of the Kingdom of Heaven (D2), meaning that leaders of GKPB Bali had practiced the Jesus transformative leadership model. However, the adequate salary and facilities provided by the synod created anthropocentric comfort, which diluted the spirit of the mission. Third, the background of "long-serving" (L5) dominantly influenced GKPB Denpasar leaders and activists to adjust Jesus’s transformative leadership model, but this was not yet able to fully optimize the practice. Therefore, GPKB Denpasar leaders and activists need to shift from the traditional paradigm to the transformative one to carry out personal and institutional transformations to improve their quality, range of services and answer future challenges.